Constraints of No‐Till Dryland Agroecosystems as Bioenergy Production Systems. (1st March 2013) - Miner, Grace L.; Hansen, Neil C.; Inman, Daniel; Sherrod, Lucretia A.; Peterson, G. A.
Abstract : Soil erosion and loss of soil organic C (SOC) may limit the sustainable harvest of crop residues for biofuels from dryland systems in the semiarid Great Plains. The objective of this study was to evaluate the capabilities and constraints of harvesting residues from dryland systems. The study used observations from a long‐term experiment in Colorado to examine biomass production from wheat ( Triticum aestivum L.), corn ( Zea mays L.), and grain sorghum [ Sorghum bicolor (L.) Moench] at three no‐till sites in a winter wheat–corn–fallow (WCF) or winter wheat–sorghum–fallow cropping system. Modeling evaluated the impact of residue removal on erosion rates and SOC dynamics. The Revised Universal Soil Loss Equation and the Wind Erosion Equation were used to simulate erosion, and the DAYCENT model was used to estimate changes in SOC with residue removal. Biomass yield for WCF averaged 3.8 Mg ha −1, divided into stover and grain yields of 2.2 and 1.6 Mg ha −1 . Water erosion was not shown to constrain residue harvest, but modeling indicated unsustainable wind erosion rates after removing 10 to 30% of corn residue. Simulations showed that up to 80% of wheat straw could be harvested without exceeding sustainable wind erosion rates. The major constraint to sustainable residue harvest is a residue return rate of 2.4 Mg ha −1 yr −1 of biomass to maintain SOC.